2008
DOI: 10.1017/s0007114508998469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type and timing of oil supplements to sows during pregnancy on the growth performance and endocrine profile of low and normal birth weight offspring

Abstract: Eighty-eight multiparous sows were used to evaluate whether type and timing of oil supplementation during gestation influences the incidence of low birth weight (LBW). Sows were allocated (eight per treatment) commercial sow pellets (3 kg/d; control diet) or an experimental diet consisting of control diet plus 10 % extra energy in the form of excess pellets, palm oil, olive oil (OO), sunflower oil (SO) or fish oil; experimental diets were fed during either the first half (G1) or second half (G2) of gestation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 48 publications
(76 reference statements)
2
11
0
1
Order By: Relevance
“…This study demonstrated that piglet birth weight was increased in response to maternal OO supplementation, which was consistent with the findings of Laws et al [25], who reported that feeding OO to sows during the first half of gestation resulted in a lower percentage of low birth weight piglets. A possible explanation for this result was that OOfed sows had a lower back fat thickness gain in late gestation compared with CON-fed and FO-fed sows.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated that piglet birth weight was increased in response to maternal OO supplementation, which was consistent with the findings of Laws et al [25], who reported that feeding OO to sows during the first half of gestation resulted in a lower percentage of low birth weight piglets. A possible explanation for this result was that OOfed sows had a lower back fat thickness gain in late gestation compared with CON-fed and FO-fed sows.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the similarities in the fatty acid metabolism in human and pigs [21] and in order to test our hypothesis, this study aimed to determine the consequences of modifying the fatty acid composition of sows' diets, using dietary supplements with olive oil (OO) or fish oil (FO), during the first or the second half of gestation on the fatty acid profiles of maternal plasma and milk during lactation and in plasma of suckling neonates. The present study is a continuation of previous ones using the same treatment protocol in pregnant sows where it was found that with the exception of a slightly improved growth performance in offspring of FO fed sows, no difference was found in reproductive performance between the two groups [22][23][24][25].…”
Section: Introductionsupporting
confidence: 67%
“…This growth spurt is accompanied by subcutaneous lipid accumulation and research shows that the fatty acid profile of the nutrients supplied to the developing piglet postnatally can influence the fatty acid profile of the brain and other tissues (Amusquivar et al, 2008;Hyde et al, 2008). Hence, the piglet is an excellent model for the studies on fatty acid metabolism during the perinatal period (Purvis et al, 1982;Laws et al, 2009).…”
Section: Digestive Physiology and Metabolismmentioning
confidence: 99%